The Effect of Serine Protease Inhibitors on Visceral Pain in Different Rodent Models With an Intestinal Insult - Ceuleers, Hannah; Hanning, Nikita; De bruyn, Michelle; De Man, Joris G; De Schepper, Heiko U; Li, Qian; Liu, Liansheng; Abrams, Steven; Smet, Annemieke; Joossens, Jurgen; Augustyns, Koen; De Meester, Ingrid; et al. (Frontiers in Pharmacology, 2022)
Background Serine proteases are believed to play a key role in the origin of abdominal pain in IBD and IBS. We previously demonstrated a reduction of visceral pain in a post-inflammatory IBS rat model after a single intraperitoneal or intracolonic administration of a serine protease inhibitor. The aim of this study was to investigate the efficacy of serine protease inhibition on visceral pain in two different animal models involving a colonic insult based either on acute inflammation or on neonatal irritation. Moreover, protease profiling was explored in the acute colitis model. Methods An acute 2,4,6-trinitrobenzenesulphonic acid (TNBS) colitis rat model and a chronic neonatal acetic acid mouse model were used in this study. Visceral sensitivity was quantified by visceromotor responses (VMRs) to colorectal distension, 30 min after intraperitoneal administration of the serine protease inhibitors nafamostat, UAMC-00050 or their vehicles. Colonic samples from acute colitis rats were used to quantify the mRNA expression of a panel of serine proteases and mast cell tryptase by immunohistochemistry. Finally, proteolytic activities in colonic and fecal samples were characterized using fluorogenic substrates. Key results We showed a significant and pressure-dependent increase in visceral hypersensitivity in acute colitis and neonatal acetic acid models. UAMC-00050 and nafamostat significantly reduced VMRs in both animal models. In acute colitis rats, the administration of a serine protease inhibitor did not affect the inflammatory parameters. Protease profiling of these acute colitis animals revealed an increased tryptase immunoreactivity and a downregulation of matriptase at the mRNA level after inflammation. The administration of UAMC-00050 resulted in a decreased elastase-like activity in the colon associated with a significantly increased elastase-like activity in fecal samples of acute colitis animals. Conclusions In conclusion, our results suggest that serine proteases play an important role in visceral hypersensitivity in an acute TNBS colitis model in rats and a neonatal acetic acid model in mice. Moreover, we hypothesize a potential mechanism of action of UAMC-00050 via the alteration of elastase-like proteolytic activities in acute inflammation. Taken together, we provided fundamental evidence for serine protease inhibitors as a promising new therapeutic strategy for abdominal pain in gastrointestinal diseases.